1987
DOI: 10.1007/bf01297196
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa liver abscesses following endoscopic retrograde cholangiography

Abstract: We report a case of Pseudomonas aeruginosa liver abscesses following endoscopic retrograde cholangiopancreatography (ERCP) in a patient without evidence of biliary tract disease and of any known cause of hepatic infection. Computer tomography (CT) scan was the best method of diagnosis, allowing, through guided percutaneous puncture of the abscesses, isolation of the organism, which was sensitive to carbenicillin. One month of antibiotherapy with repeated aspirations of the largest abscesses was successful. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 11 publications
0
12
0
2
Order By: Relevance
“…Hepatitis B [12], Hepatitis C [13][14][15], HIV [16,17]), Bakterien (z. B. Salmonellen [18][19][20][21], Mykobakterien [22][23][24], Pseudomonaden [25][26][27][28][29][30][31][32][33], Helicobacter pylori [34][35][36][37]), Protozoen (z. B. Cryptosporidien [38,39]), Pilze [40,41] und Würmer (z.…”
Section: Involvierte Mikroorganismenunclassified
“…Hepatitis B [12], Hepatitis C [13][14][15], HIV [16,17]), Bakterien (z. B. Salmonellen [18][19][20][21], Mykobakterien [22][23][24], Pseudomonaden [25][26][27][28][29][30][31][32][33], Helicobacter pylori [34][35][36][37]), Protozoen (z. B. Cryptosporidien [38,39]), Pilze [40,41] und Würmer (z.…”
Section: Involvierte Mikroorganismenunclassified
“…Other post-ERCP infectious complications include acute cholecystitis, with incidences ranging from 0.1% to 5.9% (296-299, 314, 321, 326, 327); liver abscess (296,298,328,329); and infection of pancreatic pseudocysts (297,314).…”
Section: Diagnostic and Therapeutic Upper Gastrointestinal Endoscopymentioning
confidence: 99%
“…Endoscopy with or without invasive procedures, like biopsy, polypectomy, hemostasis and foreign body removal, were also determined by specific codes: 28030C (endoscopic biopsy); 47043B (endoscopic hemostasis); 47074C (panendoscopic polypectomy); 47083C (UGI foreign body removal); 28031C (colonoscopic or enteroscopic biopsy); 49014C (colonoscopic polypectomy); 49023C (rectoscopic hemostasis); 49025C (colonoscopy with removal of a foreign body); and 49026C (endoscopic hemostasis for colon bleeding). Because PLA had already been demonstrated as a complication of ERCP[20-23], we identified, controlled, and excluded ERCP-related procedures, including ERCP (33024B), endoscopic retrograde pancreas drainage (33033B), endoscopic retrograde biliary drainage (56020B), endoscopic papillotomy with stone extraction (56033B), endoscopic sphincterotomy (56031B), and endoscopic nasobiliary drainage (56021B), according to the specific codes. Moreover, to control other unidentified causes, usage dependence bias and confounding factors that may promote to a diagnosis of PLA, we also controlled for the frequency of outpatient department (OPD) visits and abdominal ultrasound examinations (19001C and 19009C) during the 90 d period before the index date in a multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the documented risk factors for PLA include diabetes mellitus (DM)[1,7], end-stage renal disease (ESRD)[8,9], biliary tract infection (BTI)[10], liver cirrhosis[11,12], colorectal cancer[13-17], hepatobiliary tract cancer[18,19], and endoscopic retrograde cholangiopancreatography (ERCP)-related biliary tract procedures[20-23]. In addition, serial case reports have also demonstrated that acute appendicitis or diverticulitis may result in PLA through bacterial spreading from portal systems[24-29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation